Embedded System Application for Blind People Navigation Tool - Wakhyu Dwiono; Siska Novita Posma; Arif Gunawan (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The stick for blindman navigational aid can only provide information about the presence of objects that being touched. This navigational aid stick can not provide more information such as object distance and the name of the place. To overcome this problem, we realized a navigational tool that can provide information about the distance of objects around the user and the name of the places where being passed. The existing objects are detected using three sets of ultra sonic sensors. These sensors emit ultrasonic signals, when the signal collide the obstacle, then will be reflected back and being received by these sensors too. The time lag between the transmitting and receiving signals then will be converted into the distance. RFID reader is used to read the presence or absence of tags around the RFID reader. Identity tag emits a signal that will be used to mark the place name. The results of measuring distance and sequence voice database recorder gives a good yield. Voice database recorder circuit works as well as the detection of RFID tags.